The Development and Perception of The Use of Virtual Reality Learning Kits for Electromagnetic Induction - A. B. Pakuradin; I. R. Mustapa; N. S. Y. Abdullah (PILLAR OF PHYSICS EDUCATION, 2021)
This study aims were to develop a virtual reality learning kit for teaching and learning in Electromagnetic Induction and to determine the perception of the use of the VR video from the perspective of undergraduate Physics students. This research implements development research design by utilizing the ADDIE model which involves five phases which are analysis, design, development, implementation, and evaluation. Convenient sampling techniques were used in this study. A total of 35 undergraduate Physics students in their fifth and sixth semesters of study from one of the public universities in Malaysia were selected. Research instruments used are the expert validity forms and the usability questionnaires. Collected data were then analysed using Statistical Package for Social Science (SPSS) software for validity, reliability, and usability analysis. The findings of the study show that the usability instrument has high reliability with a Cronbach's Alpha value of 0.898.  On the other hand, the developed virtual reality learning kits have high validity with 97.0% of the agreement for face validity and 95.1% for content validity respectively while the usability of this virtual reality learning kit is at a high level of agreement with a mean score of 3.37. This virtual reality learning kit helps students in reviewing their lessons on mobile with flexible time. Hence, this will indirectly increase students' motivation to learn the topic of electromagnetic induction in an interesting and fun environment.